Urban political structure and inequality: Political economy lessons from early modern German cities - Felix Schaff (European Historical Economics Society (EHES), 2022)
What was the impact of urban political structure on economic inequality in preindustrial times? I document that more closed political institutions were associated with higher economic inequality in a panel of early modern German cities. To investigate the mechanisms behind that macro-relationship, I construct a unique individual-level panel-dataset, containing c.27,000 observations on personal wealth and political office-holding in the city state of Nördlingen from 1579 to 1700. I employ a difference-in-differences setting to show that political elites enriched themselves substantially after entering office. Individuals with higher political power enriched themselves more. These private gains from public office contributed to economic inequality. To mitigate concerns about reverse causality, I exploit the Thirty Years' War (1618-1648) as a plausibly exogenous shock to elites' potential for rent-seeking. Political office-holders manipulated this crisis to enrich themselves further, contributing to an unequal wealth distribution. The results are hard to square with a common historical narrative suggesting that urban political elites were "civic-minded" guardians of the common good.
Keywords: D31; D72; H20; N43; N93; P48; 330; Wealth; Inequality; Elites; Political Economy; Rent-Seeking; Cities